Melt infiltration of the lower lithosphere beneath the Tanzania craton and the Albertine rift inferred from S receiver functions - Ingo Wölbern; Georg Rümpker; Klemens Link; Forough Sodoudi (Geochemistry, Geophysics, Geosystems, 2012)
The transition between the lithosphere and the asthenosphere is subject to numerous contemporary studies as its nature is still poorly understood. The thickest lithosphere is associated with old cratons and platforms and it has been shown that seismic investigations may fail to image the lithosphere‐asthenosphere boundary in these areas. Instead, several recent studies have proposed a mid‐lithospheric discontinuity of unknown origin existing under several cratons. In this study we investigate the Tanzania craton in East Africa which is enclosed by the eastern and western branches of the East African Rift System. We present evidence from S receiver functions for two consecutive discontinuities at depths of 50–100 km and 140–200 km, which correspond to significant S wave velocity reductions under the Tanzania craton and the Albert and Edward rift segments. By comparison with synthetic waveforms we show that the lower discontinuity coincides with the LAB exhibiting velocity reductions of 6–9%. The shallower interface reveals a velocity drop that varies from 12% beneath the craton to 24% below the Albert‐Edward rift. It is interpreted as an infiltration front marking the upper boundary of altered lithosphere due to ascending asthenospheric melts. This is corroborated by computing S velocity variations based on xenolith samples which exhibit a dense system of crystallized veins acting as pathways of the infiltrating melt. Mineral assemblages in these veins are rich in phlogopite and pyroxenite which can explain the reduced shear wave velocities. Melt infiltration represents a suitable mechanism to form a mid‐lithospheric discontinuity within cratonic lithosphere that is underlain by anomalously hot mantle.